The Aesthetics of Violence in the Case of Gaius Martius Coriolanus - Stavelas, Apostolos N. (Peitho. Examina Antiqua, 2016)
In the story of Coriolanus, as depicted mainly by Plutarch and Shakespeare, we become aware of the norms and parameters of the nobility, the sincerity and the legitimacy of violence, both in diction and action, both political and personal, both as a rhetorical strategy and as a way of living. These attributes indicate a firm culture of violence and a definite system of values, which, within the span of Roman antiquity and history, comprises an early idea of chivalry and which aims at gloria.